The Effect Of Information Technology Advancement, Personal Engineering Capabilities, and Accounting Information System User Participation on Accounting Information System Effectiveness - L.G.P Sri Eka JAYANTI; Ni Luh Kade Dinda DAMAYANTI; A.A Ayu Erna TRISNAWATI; I Ketut Puja Wirya SANJAYA (Indonesia Strategic Sustainability, 2022)
This study aims in this study to determine the effect of sophistication of information technology, personal technical ability and participation of users of accounting information systems on the effectiveness of accounting information systems. The population in this study are employees of the Village Credit Institution (LPD) in the District of Clan with sample which used that is as much 78 person respondents. The data analysis technique used in this research is Multiple Linear Regression, F-Coefficient and t-test. Based on the results of the study, it can be seen that: (1) sophistication technology information take effect positive and significant to system effectiveness information accountancy, where obtained coefficient regression 0.468 and sig 0.039. (2) the ability of personal techniques has a significant positive effect on the effectiveness of information systems accountancy, where obtained coefficient regression as big as 0.568 and sig 0.022. (3) the participation of users of accounting information systems has a significant positive effect on the effectiveness of accounting information systems, where the regression coefficients are 0.273 and sig 0.039. The magnitude of the influence of the independent variable on the sophistication of information technology is 57.1%. Suggestions that can be given by researchers are Lpada Village Credit Institutions (LPD) in Marga District in increasing the effectiveness of accounting information systems can be done by increasing the sophistication of information technology, personal technical skills and participation of users of accounting information systems.